Independent writing tasks vs. integrated writing tasks: the cognitive demands and their impacts on linguistic complexity in EFL writing - Zhao, Ziming; Nimehchisalem, Vahid; Chan, Mei Yuit (Academy Publication, 2024)
Despite many studies investigating the effects of task complexity on L2 writing performance, little attention has been given to the specific effects of independent vs. integrated writing tasks and their cognitive demands on EFL learners. This study aimed to address this gap by conducting a comprehensive examination of the cognitive demands exerted by these two types of writing tasks and their effects on linguistic complexity outcomes among 35 Chinese EFL learners. Employing mixed methods involving learner self-ratings, expert judgments, and dual-task measures, the study revealed that, compared to the independent writing task, the integrated writing task places higher cognitive demands on students. In terms of written performance, participants demonstrated enhancements in lexical and syntactic complexity when responding to the integrated writing task, supporting Robinson’s Cognition Hypothesis (CH). These findings highlight the importance of understanding the cognitive load imposed by different types of writing tasks and offer implications for educators in the design and sequencing of writing tasks within Task-Based Language Teaching (TBLT) contexts.